Complications are reduced with a protocol to standardize timing of fixation based on response to resuscitation. Issue 1 (December 2015) - Vallier, Heather; Moore, Timothy; Como, John; Wilczewski, Patricia; Steinmetz, Michael; Wagner, Karl; Smith, Charles; Wang, Xiao-Feng; Dolenc, Andrea
Abstract Background Our group developed a protocol, entitled Early Appropriate Care (EAC), to determine timing of definitive fracture fixation based on presence and severity of metabolic acidosis. We hypothesized that utilization of EAC would result in fewer complications than a historical cohort and that EAC patients with definitive fixation within 36 h would have fewer complications than those treated at a later time. Methods Three hundred thirty-five patients with mean age 39.2 years and mean Injury Severity Score (ISS) 26.9 and 380 fractures of the femur (n  = 173), pelvic ring (n  = 71), acetabulum (n  = 57), and/or spine (n  = 79) were prospectively evaluated. The EAC protocol recommended definitive fixation within 36 h if lactate <4.0 mmol/L, pH ≥7.25, or base excess (BE) ≥−5.5 mmol/L. Complications including infections, sepsis, DVT, organ failure, pneumonia, acute respiratory distress syndrome (ARDS), and pulmonary embolism (PE) were identified and compared for early and delayed patients and with a historical cohort. Results All 335 patients achieved the desired level of resuscitation within 36 h of injury. Two hundred sixty-nine (80 %) were treated within 36 h, and 66 had protocol violations, treated on a delayed basis, due to surgeon choice in 71 %. Complications occurred in 16.3 % of patients fixed within 36 h and in 33.3 % of delayed patients (p  = 0.0009). Hospital and ICU stays were shorter in the early group: 9.5 versus 17.3 days and 4.4 versus 11.6 days, respectively, bothp  < 0.0001. This group of patients when compared with a historical cohort of 1443 similar patients with 1745 fractures had fewer complications (16.3 versus 22.1 %, p  = 0.017) and shorter length of stay (LOS) (p  = 0.018). Conclusions Our EAC protocol recommends definitive fixation within 36 h in resuscitated patients. Early fixation was associated with fewer complications and shorter LOS. The EAC recommendations are safe and effective for the majority of severely injured patients with mechanically unstable femur, pelvis, acetabular, or spine fractures requiring fixation.